Association Between Nonselective Beta-Blocker Use and Hepatocellular Carcinoma in Patients With Chronic Hepatitis B Without Cirrhosis and Decompensation - Cheng, He-Yun; Lin, Hsiu C.; Lin, Hsiu L.; Uang, Yow S.; Keller, Joseph J.; Wang, Li H. (Frontiers in Pharmacology, 2022)
Nonselective beta-blockers (NSBBs) have been reported to reduce the incidence or mortality of certain types of cancers, and some studies showed NSBBs have a protective effect of hepatocellular carcinoma (HCC) in patients with cirrhosis. However, the potential preventive effect of NSBBs has not been investigated in patients with chronic hepatitis B (CHB) who have a high HCC risk regardless of the presence of underlying cirrhosis. The aim of this study was to evaluate the association between NSBB use and HCC incidence in patients with CHB without cirrhosis and decompensation. From the 2000 Longitudinal Generation Tracking Database, we enrolled patients who were newly diagnosed as having CHB from January 2001 to December 2006 and then followed them up for 10 years. To estimate the causal effect of NSBBs on the time-to-event outcomes of HCC, a marginal Cox proportional hazards model was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). After adjustment, no significant benefit of HCC risk reduction was observed between NSBB and nonusers (adjusted HR, 0.82; 95% CI, 0.52–1.31). The cumulative defined daily dose (cDDD) analysis showed no significant dose correlation among the three groups (adjusted HR [95% CI]: 1.08, [0.56–2.05], 0.54 [0.17–1.77], and 0.76 [0.40–1.42] in the <90 cDDD, 90 to <180 cDDD, and ≥180 cDDD groups, respectively). Duration-dependent associations were not observed. Multivariable stratified analyses demonstrated that HCC risk remarkably decreased in patients aged >55 years (adjusted HR, 0.49; 95% CI, 0.25–0.96; P = 0.04). In conclusions, NSBB did not significantly prevent HCC in patients with CHB infection without cirrhosis and decompensation. This study provided a valuable result that if it is required to use NSBBs as recommended chemoprevention for HCC for high-risk patients in clinical practice.